A left pulmonary artery sling with left bronchiectasis in an adult patient: A case report and review of literature. Issue 1 (12th December 2022) - Lv, Lin; Cheng, Xue; Yu, Xiaohui; Cui, Chen; Ji, Wenwen; Wang, Na; Li, Tingting; Liu, Jia; Shi, Zhihong
Abstract: Pulmonary artery sling (PAS) is a rare congenital vascular anomaly, and is usually diagnosed during the infantile or fetal period. Adult presentation of PAS is rare. We report a 55‐year‐old woman with left pulmonary artery sling and left lung bronchiectasis, performing as persistent shortness of breath, coronary computed tomography angiography (CTA) showed the aberrant left pulmonary artery emerging from the right pulmonary artery and crossing to the left between the trachea and oesophagus. We experienced a rare adult case with LPAS and left bronchiectasis, stressing the importance of the anatomic abnormalities in such cases. Abstract : We report a 55‐year‐old woman with left pulmonary artery sling and left lung bronchiectasis, performing as persistent shortness of breath, coronary computed tomography angiography (CTA) showed the aberrant left pulmonary artery emerging from the right pulmonary artery and crossing to the left between the trachea and esophagus. We experienced a rare adult case with LPAS and left bronchiectasis, stressing the importance of the anatomic abnormalities in such cases.